2021
DOI: 10.1044/2020_jslhr-20-00095
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and the Impact of Stuttering in Children Aged 8–14 Years

Abstract: Purpose The goal of this study was to evaluate possible associations between child- and mother-reported temperament, stuttering severity, and child-reported impact of stuttering in school-age children who stutter. Method Participants were 123 children who stutter (94 boys and 29 girls) who were between 9;0 and 14;10 (years;months) and their mothers. Temperament was assessed with the revised child and parent version of the Early Adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
0
15
1
Order By: Relevance
“…The present findings do not support significant differences between CWS and controls on temperament scores as measured by the CBQ. While previous research reported differences between CWS and their control peers on various tasks or instruments that measure temperament (for a review, see Conture et al, 2013 ), other studies have failed to find differences between these groups ( Reilly et al, 2013 ; Kefalianos et al, 2017 ; Walsh et al, 2019 ; Eggers et al, 2021 ). It is important to note that the studies of temperament in CWS vary greatly in their methods of sampling (e.g., the children recruited through a clinic vs. from a community sample), age range, and as pointed out by Alm (2014) , sample sizes as well as the specific test to measure temperamental differences.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings do not support significant differences between CWS and controls on temperament scores as measured by the CBQ. While previous research reported differences between CWS and their control peers on various tasks or instruments that measure temperament (for a review, see Conture et al, 2013 ), other studies have failed to find differences between these groups ( Reilly et al, 2013 ; Kefalianos et al, 2017 ; Walsh et al, 2019 ; Eggers et al, 2021 ). It is important to note that the studies of temperament in CWS vary greatly in their methods of sampling (e.g., the children recruited through a clinic vs. from a community sample), age range, and as pointed out by Alm (2014) , sample sizes as well as the specific test to measure temperamental differences.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the possible association between temperament and impact of stuttering is sparse, with a small number of studies that have been carried out reporting associations in adolescents and adults who stutter (Bleek et al, 2012;Lucey et al, 2019;Stipdonk et al, 2014) and school-age CWS (Eggers et al, 2021). Eggers et al (2021) investigated the relationship between temperament and stuttering impact using parent-and self-report questionnaires in a UK clinical cohort of school aged CWS (N = 123; aged 9;00 − 14;10 years).…”
Section: Temperament and Impact Of Stutteringmentioning
confidence: 99%
“…Research investigating the possible association between temperament and impact of stuttering is sparse, with a small number of studies that have been carried out reporting associations in adolescents and adults who stutter (Bleek et al, 2012;Lucey et al, 2019;Stipdonk et al, 2014) and school-age CWS (Eggers et al, 2021). Eggers et al (2021) investigated the relationship between temperament and stuttering impact using parent-and self-report questionnaires in a UK clinical cohort of school aged CWS (N = 123; aged 9;00 − 14;10 years). Findings indicated that an increased impact of stuttering, measured by the Overall Assessment of the Speaker's Experience of Stuttering (Yaruss & Quesal, 2016) was associated with higher negative reactivity (from parent-and self-report measures) and lower positive reactivity (self-report only), as measured using the Early Adolescent Temperament Questionnaire-Revised (Ellis & Rothbart, 2001).…”
Section: Temperament and Impact Of Stutteringmentioning
confidence: 99%
See 2 more Smart Citations